2017
DOI: 10.1007/s10033-017-0165-6
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Challenges in Developing a Smart and Effective Assistive System for Improving the Experience of the Elderly Drivers

Abstract: As the overall population ages, driving-related accidents and injuries, associated with elderly drivers, have risen. Existing research about elderly drivers mainly focuses on factual data collection and analysis, indicating the elderly's growing fatal accident rates and their different behaviours compared to younger drivers. However, few research has focused on design-led practical solutions to mitigate the elderly's growing fatal accidents, by considering their usability and body conditions, afflicting the el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Figure 7 , which is visualized from the detailed data of “ Appendix ” (Table 11 ), shows the top four evaluation methods accounted by qualitative methods: questionnaires, interviews, scenario observation, and workshops. These methods validate the effectiveness of the corresponding proposed models by capturing and communicating the participants’ feedback via different means, leading to a potential lack of robustness in research and encompassing subjectivity and bias in research conclusions (Jung et al, 2017 ; Richert et al, 2018 ; Van Acker et al, 2020 ), which is followed by insufficient generalizability, as analysed above.
Fig.
…”
Section: Literature Characterization Of Human-centred Design In Industry 40mentioning
confidence: 95%
See 2 more Smart Citations
“…Figure 7 , which is visualized from the detailed data of “ Appendix ” (Table 11 ), shows the top four evaluation methods accounted by qualitative methods: questionnaires, interviews, scenario observation, and workshops. These methods validate the effectiveness of the corresponding proposed models by capturing and communicating the participants’ feedback via different means, leading to a potential lack of robustness in research and encompassing subjectivity and bias in research conclusions (Jung et al, 2017 ; Richert et al, 2018 ; Van Acker et al, 2020 ), which is followed by insufficient generalizability, as analysed above.
Fig.
…”
Section: Literature Characterization Of Human-centred Design In Industry 40mentioning
confidence: 95%
“…Similarly, Van Acker et al ( 2020 ) concluded statistically that higher acceptability of wearable mental workload monitoring was associated with being a woman (for trust in the technology), higher technology readiness—the willingness to accept new technologies and security about private data (Victorino et al, 2009 )—and lower educational backgrounds. Besides, lack of considerations regarding specific classes of difference between humans leads to major effects on design outcomes in various design contexts: age with older people (aged 55–75 years) in safe driving (Jung et al, 2017 ) and health sector (Hoe, 2019 ); cultural influences (Russians, a Frenchman, a Chinese) in the experiment of long-term isolation in a limited room space (Boy, 2018 ). These studies address the concern that if design does appreciate individual differences towards the multidimensional approach—considering not only product and/or service design but also social aspects—this could avoid the thwarting of all research efforts and the subsequent lessening of potential benefits.…”
Section: Literature Characterization Of Human-centred Design In Industry 40mentioning
confidence: 99%
See 1 more Smart Citation
“…Studies covering all ages, or those based on other data sources, such as questionnaires and driving simulators, were eliminated. Among the literature, we found five literature reviews on the topic of traffic safety for the elderly (Ang, Chen et al, 2017;Azami-Aghdash, Aghaei et al, 2018;Fitzpatrick and O'Neill, 2017;Furtado, Lima et al, 2019;Jung, Meng et al, 2017). These review the following five aspects, respectively: the influencing factors of road traffic crashes in older adults, epidemiological models and interventions to prevent road traffic injuries among the elderly, trends and factors in ageing motorcyclists' collisions, demographic and sociological characteristics of the elderly injured in traffic crashes, and intelligent vehicle technologies to improve the driving experience of elderly road users.…”
Section: Methodsmentioning
confidence: 99%